Peran Pancasila Sebagai Upaya Membangun Etika Anak Berkebutuhan Khusus Di Masyarakat - Nida Nur Azizah Putri; Kesya Adelia Avianika; Maulia Depriya Kembara (International Forum of Researchers and Lecturers, 2023)
There are many problems of deviance that can affect the character building of young people in Indonesia. Thus, learning ethics needs to be given to a child, including children with special needs. This literature review aims to obtain information about the role of Pancasila as an effort to build the ethics of children with special needs to be able to get along in the community. This research uses 6 reference sources, with source searches through google scholar. The results of this study inform that it is very important to foster national awareness and insight, especially in special schools, especially for children with emotional disability (Tunalaras). Efforts to build children's character are carried out through Pancasila Character Learning, especially for those with emotional difficulties. the purpose of Pancasila character education is to instill moral values and good habits in students so that they can feel positive values and get used to acting in a good way based on their religion and customs.